The Impact of COVID – 19 First Outbreak on Greek Private High Schools & The Distance Learning Experience - Malagkoniari, Maria; Deliou, Cleopatra (International Conference on Business and Economics - Hellenic Open University, 2023)
Although when we speak of COVID – 19 the main affect concerns the health of individuals, it is clear that the pandemic has also affected many aspects of life such as the educational sector. Both teachers and students in Greece faced the challenge of the implementation of distance learning, national wide, during the pandemic. There is still a lack of a proper theoretical model and comprehensive scientific tools to measure the impact of COVID – 19 in education. The purpose of this research is to study and analyze whether distance learning affected the Greek private high schools in different ways such as in terms of students’ graduation or their success rate in the PanHellenic Exams, during the first outbreak of the COVID-19 pandemic. Based on literature and feedback received from high schools’ principals we captured important results over the use of distance learning and its effectiveness. More specifically, through the quantitative study performed on 63 out of 79 private high schools’ principals, the researchers reached the conclusion that the majority of private schools managed distance education successfully. It was proved that both teaching and administrative staff were highly competent and skilled in the use of new technologies and therefore, distance education was not treated as a problematic situation but it steadily became part of each school’s daily routine. EL Classifications: Μ19 (M: Business Administration and Business Economics/ Marketing/ Accounting/ Personnel Economics – Μ1: Business Administration – M19: Others) Key words: Distance Education, COVID – 19 Pandemic, Greek Private High Schools, Principals